The US presidency : power, responsibility, and accountability / E. Thomas Sullivan, University of Vermont, Richard W. Painter, University of Minnesota. - Sullivan, E. Thomas; Painter, Richard W., 1961- (Cambridge University Press, 2026)
In The U.S. Presidency, E. Thomas Sullivan and Richard W. Painter examine the evolving state of presidential power in the United States, specifically facilitating discussion and debate concerning the power, responsibility, and accountability of U.S. Presidents. How is power acquired? How is it used or misused? How are the President's powers checked and how are they held accountable to and by the people? Rather than promote a single theory of presidential power, Sullivan and Painter answer these questions with a wide range of arguments for and against power in a broad number of circumstances and Supreme Court holdings. Grounded in the intersection of law, politics, and history, this book engages readers across disciplines, helping them understand the remarkable transformation of the United States presidency. Objective and timely, The U.S. Presidency makes a case for a democratic model of self-government centered on accountability and the rule of law.